Construction and iterative redesign of synXVI a 903 kb synthetic Saccharomyces cerevisiae chromosome - Hugh D. Goold; Heinrich Kroukamp; Paige E. Erpf; Yu Zhao; Philip Kelso; Julie Calame; John J. B. Timmins; Elizabeth L. I. Wightman; Kai Peng; Alexander C. Carpenter; Briardo Llorente; Carmen Hawthorne; et al. (Nature Communications)
Abstract The Sc2.0 global consortium to design and construct a synthetic genome based on the Saccharomyces cerevisiae genome commenced in 2006, comprising 16 synthetic chromosomes and a new-to-nature tRNA neochromosome. In this paper we describe assembly and debugging of the 902,994-bp synthetic Saccharomyces cerevisiae chromosome synXVI of the Sc2.0 project. Application of the CRISPR D-BUGS protocol identified defective loci, which were modified to improve sporulation and recover wild-type like growth when grown on glycerol as a sole carbon source when grown at 37˚C. LoxPsym sites inserted downstream of dubious open reading frames impacted the 5’ UTR of genes required for optimal growth and were identified as a systematic cause of defective growth. Based on lessons learned from analysis of Sc2.0 defects and synXVI, an in-silico redesign of the synXVI chromosome was performed, which can be used as a blueprint for future synthetic yeast genome designs. The in-silico redesign of synXVI includes reduced PCR tag frequency, modified chunk and megachunk termini, and adjustments to allocation of loxPsym sites and TAA stop codons to dubious ORFs. This redesign provides a roadmap into applications of Sc2.0 strategies in non-yeast organisms.